Fast infant pain detection method - Muhammad Naufal, Mansor; Syahryull Hi-Fi Syam, Ahmad Jamil; Ahmad Kadri, Junoh; Muhammad Nazri, Rejab; Addzrull Hi-Fi Syam, Ahmad Jamil; Jamaluddin, Ahmad (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org